WIJI TUKUL: PUISI DAN HERMENEUTIKA KRITIS PUISI “PERINGATAN” KARYA WIJI TUKUL DAN PERJUANGAN POLITIKNYA DALAM PERSPEKTIF HERMENEUTIKA KRITIS JÜRGEN HABERMAS - Ferdian Dwi Prastiyo (Arete, 2020)
This paper wants to show that Wiji Tukul’s poems can be interpreted as an attempt to describe the situation of society and invite its readers to seek libera- tion from false consciousness. The research method used in this paper is critical hermeneutics focused on the idea of Juergen Habermas. Here, this paper points out that the society of Wiji Tukul’s lifetime in general has been immersed in a false consciousness that is believed ideologically. In that situation, everydayness is con- sidered normal and just even though it is an injustice situation. In critical herme- neutic point of view, this paper points out that Wiji Tukul with his poems invites public to rethink the normal situation that occurs in daily life and encourages the reader to overcome the situation. From the eJorts to overcome the situation, the emancipatory movement will rise changes in society.